2013
DOI: 10.3390/ijms14011713
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/CXCL12 in Non-Small-Cell Lung Cancer Metastasis to the Brain

Abstract: Lung cancer represents the leading cause of cancer-related mortality throughout the world. Patients die of local progression, disseminated disease, or both. At least one third of the people with lung cancer develop brain metastases at some point during their disease, even often before the diagnosis of lung cancer is made. The high rate of brain metastasis makes lung cancer the most common type of tumor to spread to the brain. It is critical to understand the biologic basis of brain metastases to develop novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 99 publications
1
34
0
2
Order By: Relevance
“…Cancer cells utilize aberrant CXCR4 expression and function to direct tissue specific metastasis [84,85]. CXCR4 is expressed in hematopoietic malignancies, such as CLL [88], and non-hematopoietic cancers, such as breast and melanoma [88], aiding in their survival and trafficking from the primary tumor to a secondary site, such as lung, bone, and brain [84,85,88,89]. …”
Section: How Ifn1 Can Suppress the Homing Of Mccs To The Distant Smentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells utilize aberrant CXCR4 expression and function to direct tissue specific metastasis [84,85]. CXCR4 is expressed in hematopoietic malignancies, such as CLL [88], and non-hematopoietic cancers, such as breast and melanoma [88], aiding in their survival and trafficking from the primary tumor to a secondary site, such as lung, bone, and brain [84,85,88,89]. …”
Section: How Ifn1 Can Suppress the Homing Of Mccs To The Distant Smentioning
confidence: 99%
“…Experiments using mouse orthotopic transplantation models have revealed that both blood flow directionality and cell surface protein expression contribute to successful homing [8991]. The highly metastatic breast cancer cell line MDA-MB-231 is comprised of a highly heterogeneous population of cells, in which single-cell-derived progenies possess specific tissue tropisms [91].…”
Section: How Ifn1 Can Suppress the Homing Of Mccs To The Distant Smentioning
confidence: 99%
“…The SDF-1/CXCR4 axis participates in lung cancer metastasis probably by regulating tumor neovascularization, basement membrane degradation, cell proliferation, apoptosis, migration, adhesion, selective metastasis to specific organs, etc. (24). The influence of SDF-1 on cell proliferation remains controversial, but the SDF-1/CXCR4 signaling pathway indeed stimulates the proliferation of prostate cancer, glioma, astrocytoma and ovarian epithelial carcinoma cells (25).…”
Section: A B Cmentioning
confidence: 99%
“…Tato vzájemná interakce také napomáhá adhezi CTC k endoteliálním buňkám, podporuje extravazaci a následně i ukotvení k ECM a stromálním buňkám. Význam receptoru CXCR4 pro metastazování nádorů prsu, prostaty, plic, kolorekta a mnoha dalších byl potvrzen řadou studií [36][37][38]. Inhibice interakce CXCR4-CXCL12 in vivo vedla k význam-nému snížení metastazování nádoro-vých buněk prsu do lymfatických uzlin a plic [39].…”
Section: Osídlení Pre-metastatické Niche Dormance a Reaktivaceunclassified